Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Reflecting a function over the [tex]\( y \)[/tex]-axis involves replacing every [tex]\( x \)[/tex] in the function with [tex]\(-x\)[/tex].
The original function is:
[tex]\[ f(x) = 5 \left(\frac{1}{5}\right)^x \][/tex]
To reflect this function over the [tex]\( y \)[/tex]-axis, we replace [tex]\( x \)[/tex] with [tex]\(-x\)[/tex]:
[tex]\[ f(-x) = 5 \left(\frac{1}{5}\right)^{-x} \][/tex]
Next, we simplify the expression [tex]\( \left(\frac{1}{5}\right)^{-x} \)[/tex]:
[tex]\[ \left(\frac{1}{5}\right)^{-x} = \left(\frac{5}{1}\right)^x = 5^x \][/tex]
So the reflected function becomes:
[tex]\[ f(-x) = 5 \cdot 5^x = 5(5^x) \][/tex]
Thus, the correct equation that represents the reflected function is:
[tex]\[ f(x) = 5(5)^x \][/tex]
Let's verify the options given:
1. [tex]\( f(x) = \frac{1}{5}(5)^{-x} \)[/tex] – This is not correct because it does not match the form we derived.
2. [tex]\( f(x) = \frac{1}{5} \frac{1}{5}\left(\frac{1}{5}\right)^x \)[/tex] – This is not correct because its form does not match the reflected function.
3. [tex]\( f(x) = 5 \left(\frac{1}{5}\right)^{-x} \)[/tex] – This can be simplified to [tex]\( 5(5^x) \)[/tex], which is correct.
4. [tex]\( f(x) = 5(5)^x \)[/tex] – This matches our simplified result, so it is correct.
5. [tex]\( f(x) = 5(5)^{-x} \)[/tex] – This is not correct because it involves a negative exponent, implying a completely different transformation.
Therefore, the equations that correctly represent the reflected function are:
[tex]\[ f(x) = 5 \left(\frac{1}{5}\right)^{-x} \text{ and } f(x) = 5(5)^x \][/tex]
The original function is:
[tex]\[ f(x) = 5 \left(\frac{1}{5}\right)^x \][/tex]
To reflect this function over the [tex]\( y \)[/tex]-axis, we replace [tex]\( x \)[/tex] with [tex]\(-x\)[/tex]:
[tex]\[ f(-x) = 5 \left(\frac{1}{5}\right)^{-x} \][/tex]
Next, we simplify the expression [tex]\( \left(\frac{1}{5}\right)^{-x} \)[/tex]:
[tex]\[ \left(\frac{1}{5}\right)^{-x} = \left(\frac{5}{1}\right)^x = 5^x \][/tex]
So the reflected function becomes:
[tex]\[ f(-x) = 5 \cdot 5^x = 5(5^x) \][/tex]
Thus, the correct equation that represents the reflected function is:
[tex]\[ f(x) = 5(5)^x \][/tex]
Let's verify the options given:
1. [tex]\( f(x) = \frac{1}{5}(5)^{-x} \)[/tex] – This is not correct because it does not match the form we derived.
2. [tex]\( f(x) = \frac{1}{5} \frac{1}{5}\left(\frac{1}{5}\right)^x \)[/tex] – This is not correct because its form does not match the reflected function.
3. [tex]\( f(x) = 5 \left(\frac{1}{5}\right)^{-x} \)[/tex] – This can be simplified to [tex]\( 5(5^x) \)[/tex], which is correct.
4. [tex]\( f(x) = 5(5)^x \)[/tex] – This matches our simplified result, so it is correct.
5. [tex]\( f(x) = 5(5)^{-x} \)[/tex] – This is not correct because it involves a negative exponent, implying a completely different transformation.
Therefore, the equations that correctly represent the reflected function are:
[tex]\[ f(x) = 5 \left(\frac{1}{5}\right)^{-x} \text{ and } f(x) = 5(5)^x \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.